Perancangan Dan Analisis Statik Chassis Kendaraan Shell Eco Marathon Tipe Urban Concept - Hidayat, Taufik; Nazaruddin, Nazaruddin; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In order to realize the energy-efficient car, there are many factors to be considered. One of them is the design of the chassis structure, which serves as a place of support for all components of the vehicle and the driver. The chassis design process starts from the selection of order type, material selection, model design and continued with static analysis. Static analysis is done in a manual way by calculating and using autodesk inventor software. The process of static analysis is in the engine, driver and driver. After the static analysis process continued with the manufacture of components and assembly. Chassis made with length of chassis 2060 mm x width 600 mm. And its chassis structure uses hollow aluminum 40 mm x 40 mm x 2 mm and hollow aluminum 25 mm x 25 mm x 2 mm. Based on the results of static analysis with manual calculations, obtained the maximum stress on the main stem 18,3 MPa And deflection main stem 3.35 MPa. Analyzes by using the autodesk inventor software obtained maximum stress on the main stem 19.4 MPa And deflection on the main bar rod 3.54 mm. The result of the minimum security factor using the inventory autodesk software 10.5. It was concluded that the chassis was still within the limits allowed in load modeling as defined and the main frame proved safe to use.Key Word : Chassis, Autodesk Inventor, Stress, Deformation, Energy Saving